Injectable antibacterial Ag-HA/ GelMA hydrogel for bone tissue engineering - Wang, Jiapu; Wang, Xuefeng; Liang, Ziwei; Lan, Weiwei; Wei, Yan; Hu, Yinchun; Wang, Longfei; Lei, Qi; Huang, Di (Frontiers in Bioengineering and Biotechnology, 2023)
Abstract Building bone tissue engineering scaffolds with hydrogel as a an efficient therapeutic strategy has outstanding bionic efficiency. In the present work, a multifunctional injectable hydrogel formed by photocrosslinking was developed by introducing hydroxyapatite (HA) microspheres to Gelatin Methacryloyl (GelMA) hydrogel. The composite hydrogels exhibited good adhesion and bending resistance properties due to the existence of HA. In addition, when the concentration of GelMA is 10% and the concentration of HA microspheres is 3%, HA/GelMA hydrogel system displayed increased microstructure stability, lower swelling rate, increased viscosity, and improved mechanical properties. Furthermore, the Ag-HA/GelMA demonstrated good antibacterial activity against Staphylococcus aureus and Escherichia coli, which could significantly lower the risk of bacterial infection following implantation. According to cell experiment, the Ag-HA/GelMA hydrogel is capable of cytocompatibility and has low toxicity to MC3T3 cell. Therefore, the Ag-HA/GelMA hydrogel is expected to as a minimally invasive treatment biomaterial in bone repair fields.